2013
DOI: 10.1017/jfm.2012.550
|View full text |Cite
|
Sign up to set email alerts
|

A falling film on a porous medium

Abstract: A gravity-driven falling film on a saturated porous inclined plane is studied via a continuum approach, where the liquid and porous layers are considered as a single composite layer. Using a weighted residual technique, a two-equation model is derived in terms of the local flow rate $q(x, t)$ and the entire layer thickness $H(x, t)$. Its linear stability analysis has been satisfactorily compared to the results of the Orr–Sommerfeld problem. The principal effect of the porous substrate on the film flow is to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 32 publications
3
45
2
Order By: Relevance
“…The numerical experiment is carried out for an air-liquid system where flow parameters are selected as the viscosity ratio m = 1/m F = 100, density ratio r = 1/r F = 1000 and layer thickness ratio n = 1/9 (Frank 2006(Frank , 2008. The lower-layer liquid is chosen as a water-glycerine mixture with a density of 1070 kg m −3 , kinematic viscosity of 6.27 × 10 −6 m 2 s −1 and surface tension of 67 × 10 −3 N m −1 (Liu & Gollub 1994;Samanta et al 2013).…”
Section: Travelling Wavesmentioning
confidence: 99%
“…The numerical experiment is carried out for an air-liquid system where flow parameters are selected as the viscosity ratio m = 1/m F = 100, density ratio r = 1/r F = 1000 and layer thickness ratio n = 1/9 (Frank 2006(Frank , 2008. The lower-layer liquid is chosen as a water-glycerine mixture with a density of 1070 kg m −3 , kinematic viscosity of 6.27 × 10 −6 m 2 s −1 and surface tension of 67 × 10 −3 N m −1 (Liu & Gollub 1994;Samanta et al 2013).…”
Section: Travelling Wavesmentioning
confidence: 99%
“…In the analysis, the influence of the porous medium was usually reduced as a slip condition [35,36]. The effect of a slip on the primary instability was investigated by Samanta et al [37,38]. It was found the slip played a destabilizing role close to the instability onset, while the flow was stabilizing at larger values of the Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…Substrate heating thus introduces new modes of instability relating to convection, and lowers the critical Reynolds number. The substrate behaviour can also be altered by allowing chemical coatings, elastic deformations, or interactions with flow through porous media (Thiele et al 2009;Ogden et al 2011;Samanta et al 2011Samanta et al , 2013, which is often modelled by an effective slip condition. External fields can also be used to stabilise or destabilise the interface.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that an effective slippage takes place that enhances the instability in the sense that it reduces the critical Reynolds number. Slippage models were investigated further by Samanta et al (2011) and an alternative porous medium model is proposed and analysed by Samanta et al (2013).…”
Section: Introductionmentioning
confidence: 99%